Prevalence of elder abuse and its associated factors among the elderly in Kekirawa division of Anuradhapura district - Nanayakkara, N.K.D.S.; Gunarathna, G.K.S.D.; Sathees, S.; Kamalarupan, L. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: The population of elderly is growing rapidly. Global increase of elderly population creates various global challenges. One of the most serious problems is the rise in elder abuse. Objective: To determine the prevalence of elder abuse and its associated factors among the elderly at Kekirawa division of Anuradhapura District. Methodology: This is a community-based cross-sectional descriptive study among 371 elderly people. The data were collected using an interviewer-administered questionnaire and were analyzed using SPSS version 25. Participants were selected randomly from the list of elderly population of each Grama Niladhari division. The association between prevalence and its associated factors was determined by using the chi-square test. Results: Out of 371 participants 28.3% were above 70 years of age and mean age was 67.47(SD=5.63) years. Around half of the elderly were female (51.8%). More than one third (39.1%) of the elderly were reported to experience at least one form of abuse. Psychological abuse was more prevalent (35.8%) while none of them reported sexual abuse. Few have reported other abuses also; such as physical abuse (7.0%), financial abuse (7.5%) and neglect (16.7%). Experiencing at least one form of abuse was associated with the following factors: age, marital status, living with partner, monthly income, receiving physical/ moral support from others & presence of chronic illness. Conclusion: The prevalence of elder abuse among elderly in Anuradhapura district is high. and it is associated with several personal factors of the elderly. Immediate interventions to prevent elder abuse is mandatory. Such interventions should give special attention to the vulnerable elderly.
Keywords: Elder; Abuse; Prevalence; Elderly